2016
DOI: 10.3390/antib5020007
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of New Species Cross-Reactive Anti-Sialoadhesin Monoclonal Antibodies

Abstract: Sialoadhesin (Sn) is a surface receptor expressed on a subset of macrophages in steady state conditions. During inflammation and diseases, Sn is highly upregulated on macrophages and blood monocytes. Therefore, therapies using monoclonal antibodies (mAbs) to target Sn-positive (Sn + ) cells are a potential strategy for targeted treatment. It has been shown that Sn internalizes after binding with a mAb, though it is not clear whether this is species-specific. In this study, new Sn-specific mAbs were developed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 47 publications
(104 reference statements)
0
14
0
Order By: Relevance
“…Similarly, the surface charge of macrophages may influence phagocytosis. In our study, we used anti-Sn mAbs that interfere with the binding of sialic acids to Sn [21]. Previous studies have shown that Siglecs on cell surface can interact with negatively charged sialic acids also present on the same cell surface in cis interactions [44].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, the surface charge of macrophages may influence phagocytosis. In our study, we used anti-Sn mAbs that interfere with the binding of sialic acids to Sn [21]. Previous studies have shown that Siglecs on cell surface can interact with negatively charged sialic acids also present on the same cell surface in cis interactions [44].…”
Section: Discussionmentioning
confidence: 99%
“…Anti-hSn mAb 12A4 and anti-mSn mAb SySy94 were produced and purified as previously published [21]. F(ab') 2 fragments were produced as previously described [34].…”
Section: Production Of Antibodies and F(ab')2 Fragmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify the Sn positive and negative cells in the CD163 positive and negative cell populations in the nasal mucosa, a double IF staining was performed using goat polyclonal antibody (pAb) against human CD163 (R&D Systems, Mineapolis, MN, USA) and mouse monoclonal antibody (mAb) against porcine sialoadhesin (Sn) (clone 41D3) [27] (Table 1). For the additional characterization of the macrophages in the nasal mucosa, a frozen ventral turbinate section was stained by a triple immunofluorescence with a mouse mAb against porcine Sn (clone 41D3) and a goat pAb against human CD163 together with a mouse mAb against porcine MHCII (clone MSA3, Kingfisher Biotech, St. Paul, MN, USA) or a mouse mAb against porcine CD14 (clone MIL2) [28]; or by a triple immunofluorescence with a mouse mAb against human Sn (clone 26B2) [29] and a goat pAb against human CD163 together with a mouse mAb against human CD1c (clone L161, Biolegend, San Diego, CA, USA) ( Table 1).…”
Section: Analysis Of the Nasal Macrophage Distribution By Immunofluormentioning
confidence: 99%
“…The binding capacity of myc-tagged Biv4.40 to Sn was assessed by immunofluorescent staining. Biv4.40 was added to Snexpressing CHO cells and non-transfected CHO cells that served as negative controls (30). Cells were seeded onto coverslips and incubated at 37 • C for 24 h. Biv4.40 was added to the cells on ice for 60 min at 1 µg/mL.…”
Section: Quality Assessment Of the Sn-binding Capacity Of The Bivalenmentioning
confidence: 99%